Pelatihan Pembuatan Sauna Rempah Nusantara Di Kelurahan Tanjung Harapan Lampung Utara - Yeyen Ilmiasari; Nyang Vania Ayuningtyas Harini; Eko Abadi Novrimansyah; Sri Puji Lestari; Yuni Elmita Sari; Aji Setiya Bakti (Pengabdian Kepada Masyarakat Cendekia, 2024)
Tanjung Harapan Village is one of the villages in Kotabumi Selatan District, North Lampung Regency, Lampung Province, Indonesia. In the midst of the Covid-19 pandemic, the people of Tanjung Harapan Village, who incidentally are urban residents, who meet people every day, need to increase their body's immunity so they don't get sick easily. From Lampost data, July 2021, as many as 18 villages and sub-districts in North Lampung Regency were included in the red zone in the spread of Covid-19. Tanjung Harapan Village is included in the red zone for the spread of Covid-19 with information that the spread of the virus is out of control. One alternative to increase the body's immunity is to inhale the aroma of spices which are specially packaged in the form of the Nusantara Spice Sauna or known as a steam bath. Steam bath is a type of therapy using warm steam as a medium. People undergoing this therapy will be placed in a specially designed warm steam room. The aim of the training on making Nusantara Spice Sauna in Tanjung Harapan Village, North Lampung Regency is to increase the community's body immunity so that people become healthy and avoid the Covid-19 virus through the Lecturer Community Service program. The activity procedure is to prepare the tools and materials that have been provided. Then put the spices that have been dried or crushed into a pot that has been filled with boiling water. Close the sauna pot tightly. Install the paralon that connects the pot to the sauna room. Wait until the spice water boils. After boiling, one of the residents went into the steam room for 10-15 minutes. Residents or the public will inhale the aroma of spices, and relax the body. The practice of serving the archipelago spice sauna is for 1 resident to enter the sauna room for 10-15 minutes. Before and after entering the sauna, residents are measured by vital signs (TTV), so that the difference can be seen when taking a steam bath. However, there were 9 residents who did TTV after entering the sauna room. There were 3 people who had high blood pressure (hypertension), then entered the sauna room and their blood pressure dropped. However, there were 6 people who experienced increased blood pressure after taking a steam bath. lower than the temperature of the sauna room.